Macaronesian Muscidae (Diptera). V. The genera Phaonia Robineau-Desvoidy and Muscina Robineau-Desvoidy - Michelsen, Verner; Pont, Adrian C. (Zootaxa, 2024)
We present a review and taxonomic update of the Macaronesian species of the muscid genera Phaonia and Muscina. As a preamble we argue that Phaonia tuguriorum (Scopoli) should be considered as a senior synonym of P. scutellata (Zetterstedt) (syn. nov.) and that the name P. signata (Meigen) (sp. rev.) is reestablished as the valid name for P. tuguriorum auctt. The Azores, Canary Islands and Madeira each have three species of Phaonia and three species of Muscina. One species and three subspecies are endemic to the Canary Islands: Phaonia nigrisquama Stein, P. tuguriorum canariensis Villeneuve (stat. nov.), P. trimaculata sordidisquama Stein (stat. nov.), and Muscina prolapsa fuscisquama ssp. nov. Identification keys to males and females are given for both genera.